The effect of the simultaneous Prompting–Constant time delay instructional sequence on the teaching of early academic skills to students with intellectual disabilities. (April 2023) - Aldosiry, Norah
Abstract: This study investigated the effectiveness of combining simultaneous prompting (SP) and constant time delay (CTD) (hereafter SP–CTD instructional sequence) in teaching early academic skills to five students with intellectual disabilities (ID). A multiple-probe design was used to examine the functional relationship between the SP and CTD instructional sequence and the acquisition of letter–sound correspondences and number recognition. The results showed the effectiveness of the procedure, as all students acquired their target skills in 7–12 sessions, with an average error rate of 8%. Maintenance effects were assessed at 2, 6, and 10 weeks after the intervention to measure participants' retention of these acquired skills. Three students preserved their skills with 100% accuracy, while two students did so with more than 90% accuracy. The data indicate that instruction consisting of probe trials, 0-s trials, and 5-s trials leads to improvements in early academic skills among students with ID. Highlights: The study combined CTD and SP to teach academic skills to students with ID. The instruction structure consists of probe trials, 0-s trials, and 5-s trials. The procedure offers learners more opportunities to respond independently. The results suggest that the instruction was effective. Students acquired and maintained their early academic skills with minimal errors.